Rancang Bangun Roller Conveyor Adjustable dengan Metode Banchmarking - Ucok Simson, Simson; Azriadi, Emon; Yusnira, Yusnira (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Abstract Technology that is increasingly rapidly developing encourages all parties to compete to create or develop better technology, and has great benefits and efficiency. In these moving activities, an efficient, practical and economical means of transport is needed to facilitate the transfer process. The objectives of this research are: 1. Applying Benchmarking method in the design of adjustable roller conveyor. 2. Analyze the function and material components, and record the advantages and disadvantages. This research was conducted using the Benchmarking method, the results of this study were in the form of product designs and products for adjustable roller conveyors as material transferers. The conclusions of this study are: 1. Design of an adjustable roller conveyor based on benchmaking with two Roller conveyor tools, this tool is very well suited and very easy in the transfer process, especially for materials that are very far away. 2. The manufacture of adjustable roller conveyors has gone through an analysis process in terms of function, and the component materials used are in accordance with the aspects that have been designed with the advantages and disadvantages made.